Hygienic Risk Analysis in Sawmills (Part I) - Medina-Escobar, María de Lourdes (2014)
Respiratory and nasal cancers are among the diseases associated with occupational exposure to wood dust. This study allowed assessing, in an exploratory way, some chemical and biological agents that could be affecting the health of the mill workers. For the wood dust exposure assessments, measurement equipment to collect samples according to the method MDHS 14/3 (2000) was used, subsequently analyzed in the Laboratory of Analytical Hygiene of the ITCR and biological agents samples were analyzed according to Pouch (2003) in the Food Laboratory of the University of Costa Rica. The wood dust concentrations were found in a range of 0.09 to 28.9 mg/m3, with an MLE estimate of 2.33 mg/m3 exceeding national and international regulations. Species of fungi and bacteria were found in samples of wood dust: Aspergillus, Bacillum, and Penicillium. The detailed characterization of the presence of biological agents in the wood dust is a novel research area in the country to be taken up in future research for better understanding of their role in respiratory and immune pathology of exposed workers.